Retand LTR-retrotransposons in plants: a long way from pol to 3’LTR - Carlos M. Vicient (Mobile DNA)
Abstract Background Plant Gypsy LTR-retrotransposons are classified into lineages according to the phylogenetic relationships of the reverse transcriptase. Retand is a lineage of non-chromovirus elements characterized by the presence of a long internal region compared to other lineages. Results This work focuses on the identification and characterization of Potentially Recently Active Retand Elements (PRAREs) in 617 genomic sequence assemblies of Viridiplantae species. The Retand elements were considered PRAREs if their LTRs and insertion sequences were identical, and the sizes of their internal regions and LTRs did not differ by more than 2% from the consensus. A total of 2,735 PRAREs were identified, distributed in 122 clusters corresponding to 34 species, with copy numbers per cluster varying between 1 and 180. They are present in Eudicotyledons and Liliopsida but not in other groups of plants. Some PRAREs are non-autonomous elements, lacking some of the typical LTR retrotransposon coding domains. The size of the POL-3’LTR regions varies between 2,933 and 6,566 bp, and in all cases, includes potential coding regions oriented antisense to the gag and pol genes. 97% of the clusters contain antisense ORFs encoding the TRP28 protein domain of unknown function. The analysis of the consensus TRP28 domain indicates that it probably can bind DNA. About half of the PRAREs contain arrays of tandem repeats in the POL-3’LTR region. Conclusions The large internal region of the Retand elements is due to the presence of a long POL-3’LTR region. This region frequently contains arrays of tandem repeats that contribute to the expansion of this area. The presence of antisense ORFs in the POL-3’LTR region is also a common feature in these elements, many of which encode proteins with conserved domains, especially the TRP28 domain. The possible function of these TRP28-containing proteins is unknown, but their potential DNA binding capacity and the comparison with similar genes in some retroviruses suggest that they may play a regulatory role in the Retand transposition process.